Emotional Maieutics in creating Public Art: the “Butterfly Gate” (Itinera, 2023)
The “Porta delle farfalle” (Butterfly Gate) is a new monumental work of public art, approximately two kilometres long, that continues the “Porta della Bellezza” (Beauty Gate), which has been built and preserved for over a decade in Librino, a suburban district of the city of Catania. This project made use of an 'emotional' maieutic strategy: involving more than 15,000 people, practically no one in the community was left out.This way each citizen played a role in the change that affected both the inhabitants and the territory through a remarkable example of cooperative public art.Personally involved in the artistic and urban process, residents became part of the work, recognising themselves in symbols that range from the historical roots of the area to popular icons and images aimed at redemption and dreams.